Facies Analysis, Diagenetic Features and Depositional Environment of the Kometan Formation from Northeastern Iraq - Al-Juboury, Ali Ismail; Sulaiman, Mohamed Ali M.; Al-Mutwali, Majid M.; Rowe, Harry; Zanoni, Giovanni (Iraqi Journal of Science, 2023)
This study involves microfacies analysis of the Kometan Formation from northeastern Iraq supported by detailed petrographic investigation for the main components and diagenetic processes using a petrographic microscope, scanning electron microscope (SEM), and X-Ray diffraction (XRD). The techniques have revealed that the formation includes two microfacies; lime wackestone and lime packstone microfacies which in turn are subdivided into seven sub-microfacies, that were deposited in the quiet and deep marine environment. Planktonic foraminifera (keeled and globular chamber types) are dominant, along with oligostegina in addition to subordinate benthonic foraminifera and fine-grained bioclasts. Calcite forms the main mineralogical composition in euhedral (rhombohedral), microcrystals, star-shaped, and columnar crystals in addition to pyrite and glauconite. All components are embedded in the micritic groundmass. The main diagenetic processes affecting the studied rocks include; chemical compaction (stylolite formation), dissolution, recrystallization, and cementation.